Comparing estimates of physical activity in children across different cut‐points and the associations with weight status. (13th March 2022) - Leppänen, Marja H.; Migueles, Jairo H.; Abdollahi, Anna M.; Engberg, Elina; Ortega, Francisco B.; Roos, Eva
Abstract : This study aimed to compare sedentary time (SED) and intensity‐specific physical activity (PA) estimates and the associations of SED and PA with body mass index (BMI) and waist circumference (WC) using three different sets of cut‐points in preschool‐aged children. A total of 751 children (4.7 ± 0.9 years, boys 52.7%) wore an ActiGraph GT3X+BT accelerometer on their hip for 7 days (24 h). Euclidean norm −1 G with negative values rounded to zero (ENMO) and activity counts from vertical axis (VACounts) and vector magnitude (VMCounts) were derived. Estimates of SED and light, moderate, vigorous, and moderate‐to‐vigorous PA (MVPA) were calculated for commonly used cut‐points by Hildebrand et al., Butte et al., and Evenson et al. Furthermore, the prevalence of meeting the PA recommendation, 180 min/day of which at least 60 min/day being MVPA, were assessed for the cut‐points. Multilevel mixed analysis was used to examine associations of SED and PA with BMI and WC. In accordance with the results, SED and PA intensity estimates differed largely across cut‐points (i.e., SED = 22–341 min/day; light PA = 52–257 min/day; moderate PA = 5–18 min/day; vigorous PA = 7–17 min/day; MVPA = 13–35 min/day), and the prevalence of children meeting the PA recommendation varied from 4% to 70%. Associations of SED and PA with BMI or WC varied between the cut‐points. Our results indicate that SED and PA estimates in preschool‐aged children between studies using these cut‐points are poorly comparable. Methods facilitating accelerometer‐derived PA estimate comparison between studies are highly warranted.